Visitor Behavior in the Library of Syiah Kuala University based on Their Visiting Time Duration - Samsul Anwar; Afriyani Afriyani; Putri Shalihatul Ula; Isra Safriana; Ida Fajri; Reza Ariska (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The main requirements in the application of survival analysis are the starting time and the ending time of an event. Thus, the duration of visiting time in the Library of Syiah Kuala University (Unsyiah) Banda Aceh could be analyzed by using survival analysis. This study obtained primary data through an interview with the visitors of Unsyiah’s library. Total Samples were 105 visitors collected from three different floors of the library that is 35 visitors from each floor. The analysis was divided into two main steps. The first step was estimating the probability distribution of the visit time duration data through graphical analysis. The second step was calculating the probability density function (PDF), cumulative density function (CDF), survival, and hazard function of the data based on the appropriate distribution in the first step.